2003
DOI: 10.1034/j.1399-0004.2003.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Intact fetal cell isolation from maternal blood: improved isolation using a simple whole blood progenitor cell enrichment approach (RosetteSep)

Abstract: Isolation and analysis of intact fetal cells in maternal blood is an attractive method of non-invasive prenatal diagnosis; however, detection levels are not optimal. The poor sensitivity and inconsistent recovery of fetal cells is compounded by small numbers of circulating fetal cells and loss of fetal cells during enrichment procedures. Optimizing selection criteria by utilizing less complicated methods for target cell enrichment is essential. We report here salutary results using a simple density-based deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Likewise, foetal cells crossing the placenta barrier into the maternal peripheral blood are extremely rare -estimated to be around one per five million PBMC [2].…”
Section: Technological Achievements Within Cell Biology and Imaging Smentioning
confidence: 99%
“…Likewise, foetal cells crossing the placenta barrier into the maternal peripheral blood are extremely rare -estimated to be around one per five million PBMC [2].…”
Section: Technological Achievements Within Cell Biology and Imaging Smentioning
confidence: 99%
“…Numerous studies have shown that both fetal cells and cff DNA circulate freely in the maternal circulation (Lo et al, , 1998Bischoff et al, 2003;Bianchi, 2004). There has been much speculation as to the source of cff DNA; one possible source is fetal nucleated red blood cells, which undergo apoptosis in the maternal circulation.…”
Section: Origins Of Cell-free Plasma Dna and Identifying Biomarker Dmentioning
confidence: 99%
“…All the available information indicates that MACS technology allows the collection of cell populations significantly enriched in fetal erythroblasts or trophoblasts (19,30,(73)(74)(75). A combination of the MACS procedure with other strategies for isolation of rare cells is highly needed to obtain almost a pure cell population.…”
Section: In the Search Of A Partner For Macs And Facs: Theory And Biomentioning
confidence: 99%
“…Detection of levels of fetal cells with these two methods is however difficult in relation to the small numbers of circulating fetal cells and the loss of fetal cells during the enrichment procedures. Bischoff et al (30) reported a simple and rapid-density-based progenitor cell enrichment approach. The samples were labeled with a RosetteSep™ progenitor antibody cocktail to remove unwanted maternal white cells (mature T-cells, B-cells, granulocytes, natural killer, neutrophils and myelomonocytic cells).…”
Section: Isolation Of Intact Fetal Nucleated Red Blood Cells In Matermentioning
confidence: 99%
See 1 more Smart Citation